Particle Size Distribution in Agricultural Hillslope Soil: Case of Mechtat Kef Laatatfa, Ouled Hamla (Ne Algeria), Using Compositional and Multivariate Analysis - Abid, Chams; Zedam, Rabah; Taib, Hassan; Mazouz, El Hadi; Hadji, Rihab; Benslama, Marwa (Studia Quaternaria, 2026)
This study examines the spatial variability of soil particle-size distribution (PSD) along an agricultural hillslope at Mechtat Kef Laatatfa (Ouled Hamla, northeastern Algeria). The vertical and lateral organization of PSDs is investigated in relation to morphological setting, hydroclimatic conditions, and lithological context, which are considered the primary controls on sediment redistribution along the slope. The study aims to assess the added value of combining compositional and multivariate analytical approaches for interpreting particle-size variability in hillslope soils. Soil samples were collected from exposed horizons of three representative soil profiles and analysed using dry-sieving granulometry. Compositional data analysis (CoDA), principal component analysis (PCA), and end-member modelling analysis (EMMA) were jointly applied to disentangle granulometric patterns and transport-related processes. The results show that PSD accumulation is primarily governed by parent material erosion and slope gradient, with subsequent modification by size-selective sorting during downslope transport. A marked reduction in granulometric variability is observed from upslope to downslope positions, reflecting a systematic transition from coarse- to fine-dominated textures along the geomorphological gradient. By integrating compositional and multivariate techniques, this study provides a more robust and process-oriented interpretation of soil textural patterns along agricultural hillslopes, highlighting their relevance for understanding sediment redistribution under cultivated conditions.